Health insurance provider and endovascular treatment availability are associated with different hemodialysis vascular access profiles: A Brazilian national survey - Franco, Ricardo Portiolli; Chula, Domingos Candiota; de Moraes, Thyago Proença; Campos, Rodrigo Peixoto (Frontiers in Nephrology, 2022)
In Brazil, most hemodialysis (HD) patients are treated by the country’s public health system. However, accessibility to healthcare is different for public and private patients. This study aims to identify the profile of vascular access in Brazilian HD population. Additionally, it aims to examine the influence of public and private health insurance, accessibility to endovascular treatments, and timely arteriovenous access creation on the prevalence of tunneled catheters (TC), non-tunneled catheters (NTC), and arteriovenous access. We conducted a cross-sectional electronic survey across 834 centers. Centers were inquired about the number of public and private health insurance patients, the profile of vascular access, time for arteriovenous access creation, accessibility to TC insertion and endovascular treatment and availability of peritoneal dialysis and kidney transplantation. Logistic regression and multilevel logistic were performed to valuate possible interactions between the independent variables. A total of 7,973 patients across 47 hemodialysis centers were included in the survey. Public patients accounted for 77% of the study sample. The overall vascular access profile of public and private insurance groups was significantly different (p<0.001). For public health insurance patients, the prevalence of any catheter was 25%, while that for private patients was 31.8% (p<0,001). The prevalence of TC was more common in private patients (15.3% vs. 23.1%, p<0.001). The AV accesses were more common in public health patients (75% vs. 68.2%, p<0.001), as were fistulas (72.4% vs. 63.1%, p<0.001). Arteriovenous grafts were more prevalent among private insurance patients (2.6 vs. 5.1%, p<0.001). The availability of endovascular treatments increased the chance of having a TC by 2.3-fold (OR 2.33; CI 1.30-4.18); however, it did not reduce the chance of having any catheter. A high chance of having a catheter was found when the time to AV access creation exceeded 60 days. The differences between public and private patients may be explained by underpayment and decreased accessibility to care infrastructure in the public system, especially for endovascular treatments. A huge gap persists in vascular access care in Brazil between public and private patients. Thus, health policies should address the increased risk of NTC use in public health insurance patients.